PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM (STUDI KASUS PELEBARAN JALAN HR. SOEBRANTAS KOTA PEKANBARU TAHUN 2011-2014) - Rahmah Hidayati; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The background of this research with the city of Pekanbaru started growing into a big city or metropolis, as well as the population increases were higher, while the state of the land remains, it menyebkan congestion on major streets in the city of Pekanbaru. One of the development efforts within the framework of national development organized by the government is building in the public interest. The development of land requires that procurement conducted with emphasis on the principles contained in the Constitution of the Republic of Indonesia Year 1945, human rights and national land laws. The purpose of this paper is to investigate the process of land acquisition for the construction for road widening public interest in HR. Soebrantas Pekanbaru Year 2010-2013, as well as discuss the factors that influence the process of land acquisition for the construction for road widening public interest in HR. Soebrantas Pekanbaru Year 2010-2013. This study uses a qualitative model with descriptive method, which is carried out by interview, documentation, and direct observation regarding the procurement of land for construction for road widening public interest in HR. Soebrantas Pekanbaru City Year 2011-2014. Research locations in the city of Pekanbaru, the Regional Secretariat of Public Administration Section Pekanbaru. In this research method used is interactive data analysis (interactive models of analysis) of Miles and Huberman which includes data collection, data reduction, data presentation, and conclusion. Based on research that has been conducted, the results of this study indicate that the implementation of the process of land acquisition for the construction of the public interest in the widening of HR. Soebrantas Street Pekanbaru goes well, is in conformity with the existing regulations but in practice less than the maximum. Implementation of the land acquisition process is influenced by several factors, namely: planning, supervision, NJOP, community participation, and ownership of land. Keywords: land procurement, construction, public interest, Pekanbaru